Remaining of contrast dye ice cap during PVI by cryoballoon ablation; a case report - Ahmad Yamini Sharif; Entezar Mehrabi Nasab (Journal of Cardiothoracic Surgery)
Abstract Pulmonary vein isolation (PVI) with cryoballoon (CB) ablation technology is widely used to treat drug-resistant atrial fibrillation (AF). During CB ablation, there is a possibility of forming an ice cap of contrast-color on top of the balloon. If automatic balloon deflate occurs before the ice cap dissolves, embolization to the systemic circulation is possible. This case report describes the remaining of a contrast-colored ice cap to the systemic circulation in the left superior pulmonary vein (LSPV) and the remaining contrast-colored ice cap throughout the balloon deflate and its gradual melting a few seconds after the balloon deflate in the right superior pulmonary vein (RSPV). Additionally, a strategy for its prevention is presented.